Eulogy of visual literacy (ENTHYMEMA, 2021)
Recent neuroscientific advances and their application in the aesthetic and narratological fields offer a further explanation for the massive diffusion of images that has occurred in recent decades including at a narrative level. They allow us to understand even more deeply why and how we are captivated by iconic representations. The images activate mechanisms of embodied simulation of the actions, emotions and bodily sensations depicted in them. In this way the images guarantee a more 'direct' immersive experience, compared to just reading a written text. Therefore, visual storytelling is considered a proto-Adamic narrative typology compared to a written one, because visual language represents a biological and cognitive endowment available to man to convey concepts in a simplified or more emotionally attractive way. On the other hand, it is proven that when we read a text we transform concepts into images, exactly as happens in metaphors. There are several experimental studies that show the potential of visual storytelling for the development of certain skills, in particular inferential-predictive-explanatory competence; critical thinking; empathy and transportation; sequential thinking; labeling of frames and scripts;memory and learning.
Keywords: Visual storytelling; Graphic novel; front-end/back-end processes; segmentation; omission; inferential reasoning